2007
DOI: 10.1093/carcin/bgm140
|View full text |Cite
|
Sign up to set email alerts
|

ECRG2 inhibits cancer cell migration, invasion and metastasis through the down-regulation of uPA/plasmin activity

Abstract: The esophageal cancer-related gene 2 (ECRG2) is a novel gene that shows sequence similarity to KAZAL-type serine protease inhibitor. In this study, the migration and invasion of PG cancer cells were inhibited by ectopic expression of ECRG2 in vitro, and metastases decreased after injecting PG/pcDNA3.1-ECRG2 cells into the tail veins of nude mice. Control mice were injected with PG/pcDNA3.1 cells. To test the hypothesis that ECRG2 interacts with proteases and inactivates extracellular matrix degradation, bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…The ECRG4 soluble protein was used to produce polyclonal antibody in rabbit or for functional experiments. 10 Rabbit experiments were approved by the institutional review board of animal care of the Animal Center, Peking Union Medical College & Chinese Academy of Medical Sciences. …”
Section: Purification Of Ecrg4 Fusion Protein and Production Of Polycmentioning
confidence: 99%
“…The ECRG4 soluble protein was used to produce polyclonal antibody in rabbit or for functional experiments. 10 Rabbit experiments were approved by the institutional review board of animal care of the Animal Center, Peking Union Medical College & Chinese Academy of Medical Sciences. …”
Section: Purification Of Ecrg4 Fusion Protein and Production Of Polycmentioning
confidence: 99%
“…ECRG2 has been cloned in 1998 by mRNA differential display by comparing the gene expression between normal esophageal epithelia and esophageal carcinoma 9 and further studies showed that it had roles as a tumor suppressor. [4][5][6]10 It was downregulated in esophageal squamous carcinoma and other cancers. ECRG2 is important for ensuring centrosome duplication and accurate chromosome segregation, and its disruption leads to centrosome amplification and spindle checkpoint defects, contributing chromosome instability.…”
Section: Discussionmentioning
confidence: 99%
“…5 Cui et al 4 showed that ECRG2 interacted with MT2A physically and induced apoptosis of cancer cells. Further, Huang et al 6 reported that ECRG2 inhibited invasion and metastasis of lung cancer cell by suppressing urokinase-type plasmin activator/plasmin pathway. Depletion of ECRG2 contributes to lung cancer cell invasion by regulating extracellular matrix degradation, 5 representing that ECRG2 is a novel therapeutic target for cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal cancerrelated gene 2 (ECRG2), also named serine peptidase inhibitor Kazal-type 7 (SPINK7), was identified as a growth-regulating gene by comparing normal esophageal epithelia and primary squamous cell carcinomas tissues from high incidence families in Lin-Xian County of China using differentially displayed PCR (Su et al 1998;Cui et al 2010). It has been shown that ECRG2 is a tumor suppressor gene involved in the regulation of cell proliferation, induction of apoptosis, and inhibition of cancer cell migration, invasion and metastasis (Cui et al 2003;Huang et al 2007). ECRG2 also participates in centrosome amplification in a p53-dependent manner and has a role in maintaining chromosome stability (Cheng et al 2008).…”
Section: Biological Contextmentioning
confidence: 99%
“…ECRG2 also participates in centrosome amplification in a p53-dependent manner and has a role in maintaining chromosome stability (Cheng et al 2008). Recently, it was found that ECRG2 regulates cell migration/invasion through urokinase-type plasmin activator (uPA)/urokinase-type plasmin activator receptor (uPAR) pathway by directly inhibiting uPA/plasmin activity, and may represent a novel therapeutic target for cancer (Huang et al 2007;Cheng et al 2009Cheng et al , 2010Cui et al 2010).…”
Section: Biological Contextmentioning
confidence: 99%